Wanprestasi dalam Kerja Sama Pengelolaan Lahan Pertanian Sistem Perairan - Napisah; Putri Deva Hairunisa; Ria Astina; Yuswalina; Aula Sakinah (Al-Ijtima`i: International Journal of Government and Social Science, 2026)
Collaboration in agricultural land management is a common form of economic relationship in rural communities, including through the irrigation system that has developed in Suka Negeri Village. However, the implementation of such collaboration often faces issues of breach of contract due to unclear rights and obligations among the parties. In this study, we aim to analyze the fulfillment of the essential elements and conditions of the mukhabarah contract in the practice of the irrigation system, identify the forms of breach of contract that occur, and examine their implications for village life. Qualitative research was employed, utilizing semi-structured interviews with 16 informants. The results indicate that agreements are made orally without fulfilling the essential elements of the mukhabarah contract, leading to legal uncertainty and breach of contract by both parties. Such practices contradict the principles of al-wafa bi al-‘uqud and la dharara wa la dhirara in Islamic law. Policy recommendations include the requirement for written agreements and the strengthening of community-based mediation mechanisms.